2012
DOI: 10.1515/jbcpp-2012-0020
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study of the ameliorative role of α-tocopherol on methotrexate-induced oxidative stress in rat heart mitochondria

Abstract: The present study suggests that vitamin E plays a vital role in suppressing MTX-induced mitochondrial toxicity, and affords protection either by reversing the decline of antioxidants or by direct scavenging of free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(23 reference statements)
0
6
0
1
Order By: Relevance
“…Interestingly, inhibition of mtFAO has been documented with several of these drugs, namely tamoxifen, raloxifene and NRTIs [3,28,93,94]. Moreover, drugs such as tamoxifen, methotrexate and NRTIs can inhibit MRC activity and favor oxidative stress [3,16,28,95,96]. However, for some of these compounds, aggravation of preexisting NAFLD could also be secondary to other mechanisms.…”
Section: Drug-induced Inhibition Of Mtfao and Aggravation Of Nafldmentioning
confidence: 99%
“…Interestingly, inhibition of mtFAO has been documented with several of these drugs, namely tamoxifen, raloxifene and NRTIs [3,28,93,94]. Moreover, drugs such as tamoxifen, methotrexate and NRTIs can inhibit MRC activity and favor oxidative stress [3,16,28,95,96]. However, for some of these compounds, aggravation of preexisting NAFLD could also be secondary to other mechanisms.…”
Section: Drug-induced Inhibition Of Mtfao and Aggravation Of Nafldmentioning
confidence: 99%
“…In liver mitochondria, methotrexate promotes a significant rise in superoxide radical formation, as well as in lipid peroxidation, whereas the GSH levels are decreased [114]. Likewise, methotrexate significantly impairs the function of isolated heart mitochondria by promoting lipid peroxidation, mitochondrial swelling and by inhibiting complex I, II and IV activities [115].…”
Section: Folate Antagonistsmentioning
confidence: 99%
“…An in vitro study demonstrated that Vitamin E decreases the oxidative stress induced by methotrexate in rat heart mitochondria and thereby minimizes mitochondrial dysfunction [115]. Likewise, the administration of lipoic acid decreases oxidative stress induced by methotrexate, which affects liver mitochondrial function [114].…”
Section: A Mitochondrial Basis For Anticancer Drugs Combinations: a Pmentioning
confidence: 99%
“…Antioxidants have been widely used in the restoration of mitochondrial function [ 11 , 12 , 13 , 14 ]. Specifically, N -acetylcysteine (NAC), a prodrug for cysteine, is a well-known antioxidant and a precursor for the crucial intracellular antioxidant GSH [ 15 ] that protects against cellular damage caused by free radicals [ 16 ].…”
Section: Introductionmentioning
confidence: 99%